A influência do nível competitivo na percepção da síndrome de burnout em atletas universitários de handebol - SOUSA, Milene Caroline Araujo de (2019)
Sports burnout syndrome consists of a psychophysiological response to exhaustion and is based on three dimensions: physical and emotional exhaustion (EFS); reduced sense of sports achievement (RSR); and sports depreciation (DES). Its main consequences are the loss of motivation and the abandonment of the sports career. The present study aims to analyze the effect of the competitive level on the perception of burnout and its dimensions in handball university athletes. 89 athletes (45 men and 44 women) belonging to the three distinct divisions of the Brazilian University Games in Goiânia (21 from the first division, 29 from the second division and 39 from the third division) participated in the study, with a mean age of 21.76 ± 3.17 years. Athletes completed the Athlete Burnout Questionnaire (QBA) and a demographic data sheet. For the analysis of the data were used the tests of normality of Kolmogorov-Smirnov, Anova Kruskal-Wallis, and post hoc of Mann-Whitney in software GraphPad Prism. The significance level adopted was p <0.05. The results presented the following medians for the EFE, RSR and DES dimensions, respectively: first division (1.8, 2.0, 1.8), second division (1.4, 2.0, 1.8), third division (1.6, 2.4, 1.8). There were no significant differences between the first, second and third division athletes in the EFE and DES dimensions. For the RSR dimension there was no significant difference between first and second division athletes. However, athletes in the third division had higher scores of this dimension compared to their first and second division pairs, as well as a higher perception of total burnout compared to the second division athletes. Therefore, when comparing the dimensions of burnout among the three groups, we noticed that the competitive level variable, represented by the disputed division, interferes with the perception of reduced sense of sports accomplishment and total burnout, resulting in low sports accomplishment among handball athletes participants in the third (and last) division of the main Brazilian university competition.